(untitled) (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
The formulation of Production Sharing Contracts (KBH) for oil and gas in Aceh is different from other regions in Indonesia. The formulation of the KBH must be guided by Government regulation no. 23 of 2015 concerning Joint Management of Natural Oil and Gas Resources in Aceh as the legal basis for the Aceh Government in managing oil and natural gas. The preparation of the KBH in Aceh must involve the Aceh Government, especially in terms of formulating, amending and canceling the KBH. Likewise issues related to data management, payment of signature bonuses and production bonuses, audits, transfer of Participating Interest (PI), involvement of Aceh-Owned Enterprises and determination of CSR funds. So far there has only been one KBH for the Management of Oil and Gas in the Pase Block between the Aceh Regional Development Company (PDPA) and Triangle Pase Inc (TPI), which was signed on May 22 2015. In the implementation of this KBH, it was found that a number of contractual obligations had not been implemented and were even violated. by Triangle Pase Inc, causing losses to PDPA. Therefore, PDPA filed a lawsuit through BANI whose decision was to reject all PDPA claims and require them to pay arbitration costs. It is hoped that PDPA will immediately submit an annulment of BANI’s decision.